Endothelial dysfunction correlates with decompression bubbles in rats - Zhang, K.; Wang, D.; Jiang, Z.; Ning, X.; Buzzacott, Peter; Xu, W. (Nature Publishing Group, 2016)
© 2016 The Author(s). Previous studies have documented that decompression led to endothelial dysfunction with controversial results. This study aimed to clarify the relationship between endothelial dysfunction, bubble formation and decompression rate. Rats were subjected to simulated air dives with one of four decompression rates: one slow and three rapid. Bubble formation was detected ultrasonically following decompression for two hours, before measurement of endothelial related indices. Bubbles were found in only rapid-decompressed rats and the amount correlated with decompression rate with significant variability. Serum levels of ET-1, 6-keto-PGF1a, ICAM-1, VCAM-1 and MDA, lung Wet/Dry weight ratio and histological score increased, serum NO decreased following rapid decompression. Endothelial-dependent vasodilatation to Ach was reduced in pulmonary artery rings among rapid-decompressed rats. Near all the above changes correlated significantly with bubble amounts. The results suggest that bubbles may be the causative agent of decompression-induced endothelial damage and bubble amount is of clinical significance in assessing decompression stress. Furthermore, serum levels of ET-1 and MDA may serve as sensitive biomarkers with the capacity to indicate endothelial dysfunction and decompression stress following dives.